2013
DOI: 10.1126/science.1231476
|View full text |Cite
|
Sign up to set email alerts
|

Global Charcoal Mobilization from Soils via Dissolution and Riverine Transport to the Oceans

Abstract: Global biomass burning generates 40 million to 250 million tons of charcoal every year, part of which is preserved for millennia in soils and sediments. We have quantified dissolution products of charcoal in a wide range of rivers worldwide and show that globally, a major portion of the annual charcoal production is lost from soils via dissolution and subsequent transport to the ocean. The global flux of soluble charcoal accounts to 26.5 ± 1.8 million tons per year, which is ~10% of the global riverine flux of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
454
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 468 publications
(493 citation statements)
references
References 30 publications
33
454
6
Order By: Relevance
“…This suggests that the hydrodynamic transport and depositional mechanism could also be an important factor affecting the occurrence of BC and TOC and their relationships, especially in the open GOT. Actually, this good correlation between BC and bulk OM was not only noticed in the particle phase (e.g., in soil, Glaser and Amelung, 2003;Cusack et al, 2012) but also in the dissolved phase and has been reported worldwide (e.g., Dittmar et al, 2012;Jaffe et al, 2013;Ding et al, 2013Ding et al, , 2015. The close relationship between BC and bulk OM in the dissolved phase could indicate that the release and subsequent sorption and desorption processes of BC are a complex function of environmental factors and particle properties, just as for bulk dissolved OM , which suggests that the mobilization of BC and bulk OM in various matrices is also mechanistically coupled.…”
Section: Relationships Between Bc Toc and Sediment Grain Size And Pomentioning
confidence: 99%
“…This suggests that the hydrodynamic transport and depositional mechanism could also be an important factor affecting the occurrence of BC and TOC and their relationships, especially in the open GOT. Actually, this good correlation between BC and bulk OM was not only noticed in the particle phase (e.g., in soil, Glaser and Amelung, 2003;Cusack et al, 2012) but also in the dissolved phase and has been reported worldwide (e.g., Dittmar et al, 2012;Jaffe et al, 2013;Ding et al, 2013Ding et al, , 2015. The close relationship between BC and bulk OM in the dissolved phase could indicate that the release and subsequent sorption and desorption processes of BC are a complex function of environmental factors and particle properties, just as for bulk dissolved OM , which suggests that the mobilization of BC and bulk OM in various matrices is also mechanistically coupled.…”
Section: Relationships Between Bc Toc and Sediment Grain Size And Pomentioning
confidence: 99%
“…On one hand, the presence of BC in geological records since the Devonian and of millennial BC in a range of soils at global scale provides evidence that some persists for a very long time in the environment (Schmidt and Noack, 2000). On the other hand, the content of BC stored in soil is low with respect to annual production rate from wildfires, which demonstrates that large amounts are lost from soil (Schmidt and Noack, 2000;Masiello, 2004;Schmidt, 2004), possibly by microbial decomposition (Baldock and Smernik, 2002;Hamer et al, 2004;Wengel et al, 2006), erosion (Rumpel et al, 2006) or dissolution and transport with water fluxes (Hockaday et al, 2007;Jaffé et al, 2013). The longevity of BC in soil seems to depend on both intrinsic quality and the environmental conditions where it is deposited (Bird et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…biochar half-life). This technique would be particularly interesting if the emitted CO 2 is quantified and its source determined by δ 13 C measurement of the emitted CO 2 (Rittl et al, 2015b), thus allowing to estimate the real mineralization of the applied biochar, since important losses of pyrogenic C occur via dissolution and transport to rivers and sea (Jaffé et al, 2013), aside from losses by runoff (Major et al, 2010a) and bioturbation (Elmer et al, 2015).…”
Section: Quantification Of Pyrogenic Cmentioning
confidence: 99%